Суб'єктно-вчинковий вимір виховання особистості - Шульга, Вікторія; Shulha, Viktoriya (ТНЕУ, 2011)
У статті висвітлюються результати дослідження можливостей застосування у практиці освітнього процесу суб’єктно-вчинкового підходу до виховання особистості учня. Викладено основи психолого-педагогічної технології виховання на засадах спільного вчинку дорослих та дітей. In the article the results of investigation of opportunities of use in the practice of educational process the subject-action approach to the education of a pupil’s personality are demonstrated. The basis of psychological-pedagogical technology of bringing up on the grounds of common action of adults and children are given.
Subjective-actional dimension of a personality education
Keywords: особистість; сучасна психологія виховання; суб’єктно-вчинкова парадигма; суб’єкт-суб’єктна взаємодія; спільний учинок; personality; modern psychology of bringing up; subjective-actional; paradigm; subject-subjective interaction; common act